INNOVATION IN RUSSIAN PRODUCTION AND EXPORT OF GAS - Rodion M. Zhdanovskich (Вестник Российского экономического университета имени Г. В. Плеханова)
The importance of developing the natural gas liquefaction industry in the Russian Federation is caused by political and economic reasons. In contrast to pipeline export gas supply, when Russia gets into serious dependence on transit countries and  countries consuming gas liquefied natural gas (LNG) provides an  opportunity to manoeuvre volumes and directions of sales. Due to  the fact that the Asia-Pacific region is taking the leading positions in  global gas consumption Russian oil and gas companies need LNG to  re-orientate gas flows in the eastern direction. The author shows  that in order to build the advanced highly technological gas industry  Russian companies today should set the foundation for refinery of  traditional natural gas and oil gas and methane from coal layers too  get liquefied synthesis-fuel of high quality. In the near future Russia  should take a leading position in the global trade on highly technological gas produce.